Development of Android-Based Physical Activity-Augmented Reality 3D Interactive Media for Physical Education Subjects for PDPD (Students With Disabilities) in SLB to Support the MBKM Program - Nur Ahmad Muharram; Budiman Agung Pratama; Setyo Harmono (Universitas Negeri Semarang, 2024)
This study seeks to evaluate the effectiveness, appeal, and practicality of interactive learning tools utilizing Augmented Reality (AR). Employing a research and development approach, the study focuses on creating AR-based learning materials, drawing inspiration from the ADDIE development model’s Analyze, Design, and Development stages. While the traditional ADDIE model comprises five stages, this research streamlines the process to three key stages. Validation tests conducted by both media and subject matter experts confirmed the high validity of the AR-based learning materials. Media expert evaluations yielded an Aiken’s V value of 0.913, while subject matter expert assessments resulted in a value of 0.921, indicating strong validity. Subsequent tests involving 20 students with special needs from SLB Kediri City revealed high levels of attractiveness and user-friendliness, with 73% of participants finding the materials engaging and 91% expressing that they were very easy to navigate. In conclusion, the study suggests that AR-based interactive learning tools for Physical Education cater to the needs of students with disabilities in Kediri City. These tools not only capture students’ interest but also offer ease of use. However, further evaluation through classroom trials is recommended to ascertain the effectiveness of AR learning materials in enhancing learning outcomes in Physical Education.